The Fading (Lost) Colour of Reformed Theology in Reformed Churches in Indonesia and the Urgency of Reformation in the 21st Century - Lumintang, Stevri P.N. Indra (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
This study aims to reveal the fading (lost) colour of Reformed theology in churches with Reformed backgrounds or patterns in Indonesia as a reason for the urgent reformation agenda at the beginning of the 21st century (today). This objective is motivated by the gap between Reformed theology that faithfully upholds the truth of the Bible and the compromise of church leaders and/or theologians that results in the fall of the church and the loss of hope for the world (tragic). The research used historical-theology method, with the finding that the fading colour of Reformed theology in some Reformed churches denominations in Indonesia started since the entry of Reformed theology and churches that have been "castrated", taken captive (colonised) by state churches that are not interested in theology, lied to by the strong influence of modern liberal theology trends and postliberal postmodern theology trends, and fooled by the imposition of Western Christian culture and the denial of local culture, which resulted in the alienation of Reformed theology in Indonesia. This very alarming condition results in the loss of identity, guidance and the (fundamental) spiritual influence of Reformed theology. This finding is an input for the churches to be open to an urgent reformation agenda as the only solution.